CLASSROOM ENVIRONMENT, STUDENTS MOTIVATION, AND SPEAKING ANXIETY AMONG VOCATIONAL HIGH SCHOOL STUDENTS IN ENGLISH LESSON - M Fadjar Bima; Sugeng Susilo Adi (Erudio Journal of Educational Innovation, 2021)
Students in vocational high school mostly not acknowledge English language well because they are only focused in learning about the major material. In other words, while vocational high school students are learning English particularly in speaking skill there is an issue followed in acquiring the language which is speaking anxiety. Students feel anxious in speaking for the reason such as motivation and environment which make it difficult to comprehend it. This study aims at finding out the extent between classroom environment and students motivation towards speaking anxiety of vocational high school students using correlation method to discover the relationship. The subjects of this study were 105 students of first grade of beauty, culinary art major and second grade of design maker, design fashion in SMKN 3 Malang. The method of this study was quantitative with partial correlation design. This study used three kinds of questionnaire as the research instruments which are Public Speaking Class Anxiety Scale (PSCAS), Attitude/Motivation Test Battery (AMTB) and Students Satisfaction of Classroom Environment (SSCE). The collected date would be analysed using Pearson Product Moment in SPSS. This study revealed that the correlation between classroom environment and speaking anxiety is 0.172  and the significance value is 0.0089 < 0,05 that can be interpreted as positive correlation but it is very weak correlation, the correlation between motivation and speaking anxiety is - 0.139 and the significance value is 0.0170 > 0,05 that can interpreted as a negative correlation or no correlation at all.  It is shown that the correlation between classroom environment (X1) and students motivation (X2) towards speaking anxiety (Y) is rejected or there is o correlation among variables. However, the correlataion between classroom environment and motivation os 0.289 with significance value 0.003<0,05 which means weak correlation. It can be assumed that classroom environment and motivation are not really associated with students speaking anxiety.